Wellness Tourism in Bali: Is it Possible? - Wijaya, I Putu Yoga Purnama; Prianthara, I. B. Teddy (GoAcademica Research & Publishing, 2024)
Bali is known as a leading tourist destination abroad, with various attractions that attract both international and local tourists. Among these attractions, Wellness Tourism has emerged as the top choice for tourists in Bali. Wellness Tourism aims not only to promote health and wellness but also to offer unique and valuable experiences for tourists. However, despite its popularity, there has been no structured and systematic effort to integrate mental health-based tourism concepts. In addition, preserving the sacred values of local communities is important to maintain Balinese cultural heritage and wisdom. Implementing health tourism in the wrong way can threaten to undermine these sacred values, highlighting the importance of using the right marketing mix strategy. To find out more about this, a qualitative study was carried out using purposive sampling, involving observation, interviews and documentation. Analysis was carried out using NVivo software. The findings show that the development of sustainable health tourism in Bali has gone well, showing the effectiveness of the marketing mix approach without any manipulation.